2002
DOI: 10.3998/ark.5550190.0003.904
|View full text |Cite
|
Sign up to set email alerts
|

Ceric ammonium nitrate impregnated on silica gel in the removal of the tert-butoxycarbonyl group

Abstract: The tert-butoxycarbonyl group was efficiently (80-99% yields) removed from an amino, hydroxy, or mercapto functionality in organic compounds by use of 0.20 equiv of Ce(NH 4 ) 2 (NO 3 ) 6 in acetonitrile at reflux. Application of the solid-supported reagent involving the use of 0.20 equiv of Ce(NH 4 ) 2 (NO 3 ) 6 impregnated on silica gel in toluene at reflux gave the deprotected products in 90-99% yields. These reactions likely proceed through an electron transfer process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The same authors also observed the removal of t-Boc group using silica gel supported CAN as a catalyst, finding that this modification of their method considerably reduced the reaction time. 97…”
Section: T-butoxycarbonyl Group Cleavagementioning
confidence: 99%
“…The same authors also observed the removal of t-Boc group using silica gel supported CAN as a catalyst, finding that this modification of their method considerably reduced the reaction time. 97…”
Section: T-butoxycarbonyl Group Cleavagementioning
confidence: 99%
“…While CAN was already a well-known reagent for the oxidative deprotection of S,S- and O,S-acetals and ketals, the oxidative cleavage of tert -butyldimethylsilyl ethers and the removal of tert -Boc groups, to the best of our knowledge, it had not been used to unmask acetals and ketals. The surprisingly rapid and efficient deprotection of ketal 1 prompted us to investigate in greater detail the scope and limitations of this novel reaction.…”
Section: Initial Observations and Discovery Of The Stoichiometric Pro...mentioning
confidence: 99%
“…The low yield observed for this cyclisation is due to the competitive cleavage of the Boc group with the CAN leading to the decomposition of the α-AAP 13 a. [29] To avoid this side reaction, the α-AAP 13 b was prepared in a comparable yield. Treatment of the latter with CAN yielded the expected spirocyclic compound 14 b in an improved 51 % yield as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the [2,3]‐sigmatropic rearrangement took place after the addition of diethyl chlorophosphite on the ynamido‐alcohol 12 a and the resulting Boc protected α‐AAP 13 a was treated with CAN in a mixture of acetonitrile and water (2 : 1) to provide the expected spirodienone lactam 14 a in a low 36 % yield. The low yield observed for this cyclisation is due to the competitive cleavage of the Boc group with the CAN leading to the decomposition of the α‐AAP 13 a [29] . To avoid this side reaction, the α‐AAP 13 b was prepared in a comparable yield.…”
Section: Resultsmentioning
confidence: 99%